Computación de funciones de distribución - Boggia, Luis M. (1967)
We show, through concrete application, the possibilities of the GAUSS-LAGUERRE method of approximate integration at the semi-infinite intervals. The normal distribution function was tabulated in its most significant range by means of only 4 and 5 ordinates. Attached is the program used on the IBM 1620 computer belonging to the National University of La Plata (Argentina). In less than three minutes 150 integrals were calculated. The relative maximum errors were of 4% in 4 ordinates and 3% in 5 ordinates.